Mycorrhiza-Triggered Transcriptomic and Metabolomic Networks Impinge on Herbivore Fitness. Issue 4 (8th February 2018) - Kaling, Moritz; Schmidt, Anna; Moritz, Franco; Rosenkranz, Maaria; Witting, Michael; Kasper, Karl; Janz, Dennis; Schmitt-Kopplin, Philippe; Schnitzler, Jörg-Peter; Polle, Andrea
Abstract : Ectomycorrhiza-induced systemic defenses in leaves involve aldoxime metabolism and improve poplar fitness by fending off the leaf herbivore Chrysomela populi. Abstract: Symbioses between plants and mycorrhizal fungi are ubiquitous in ecosystems and strengthen the plants' defense against aboveground herbivores. Here, we studied the underlying regulatory networks and biochemical mechanisms in leaves induced by ectomycorrhizae that modify herbivore interactions. Feeding damage and oviposition by the widespread poplar leaf beetle Chrysomela populi were reduced on the ectomycorrhizal hybrid poplar Populus × canescens . Integration of transcriptomics, metabolomics, and volatile emission patterns via mass difference networks demonstrated changes in nitrogen allocation in the leaves of mycorrhizal poplars, down-regulation of phenolic pathways, and up-regulation of defensive systems, including protease inhibitors, chitinases, and aldoxime biosynthesis. Ectomycorrhizae had a systemic influence on jasmonate-related signaling transcripts. Our results suggest that ectomycorrhizae prime wounding responses and shift resources from constitutive phenol-based to specialized protective compounds. Consequently, symbiosis with ectomycorrhizal fungi enabled poplars to respond to leaf beetle feeding with a more effective arsenal of defense mechanisms compared with nonmycorrhizal poplars, thus demonstrating the importance of belowground plant-microbe associations in mitigating aboveground biotic stress.